A bidirectional association between psychotic‐like experiences and problematic Internet use: A large‐sample longitudinal study among Chinese adolescents. - Chen, Dan; Zhang, Yifan; Bu, Luowei; Ye, Haoxian; Wang, Dongfang; Fan, Fang (British Journal of Clinical Psychology, 2026)
Purpose: Psychotic‐like experiences (PLEs) are associated with problematic Internet use (PIU), but empirical studies on the causal relationships between both are lacking. This study aimed to investigate the bidirectional associations between PLEs and PIU through a large prospective study involving Chinese adolescents. Methods: A total of 27,260 adolescents (Mage = 14.3 ± 1.5 years; 47.8% of females) were assessed at baseline from December 17 to 12, 2021 (Time 1, T1) and 6 months later from May 17 to June 5, 2022 (Time 2, T2). The 8‐item Positive Subscale of the Community Assessment of Psychic Experiences and the Revised Chinese Internet Addiction Scale were used to assess PLEs and PIU, respectively. Socio‐demographics at T1 and negative life events at T2 were also evaluated. Results: Binary logistic regression indicated that PLEs at baseline significantly increased the risk of incident PIU at the 6‐month follow‐up (OR = 1.44, 95% CI = 1.25–1.66), even after adjusting for covariates. PIU at baseline was significantly associated with increased odds of incident PLEs at the 6‐month follow‐up (OR = 1.44, 95% CI = 1.14–1.82). Moreover, similar associations were also observed in the PIU and subdimensions of PLEs, that is, hallucinatory experience and delusional experience. Conclusion: This study demonstrated that the relationship between PLEs and PIU among adolescents was bidirectional. These findings have significant implications for educational and clinical strategies aimed at managing PIU and preventing PLEs among adolescents.